Murder, interrupted [compact disc, unabridged] : true-crime thrillers - Patterson, James, 1947- (Hachette Audio, 2018)
In Murder, Interrupted, rich, cheating financier Frank Howard wants his wife dead, and he is willing to pay Billie Earl Johnson whatever it takes. When his bullet misses the mark, Billie Earl and Frank will turn on each other in a fight for their lives. In Mother of All Murders, television reports praise Dee Dee Blancharde as a single mother who tirelessly cares for her wheelchair-bound, chronically ill daughter. But when the teenaged Gypsy Rose realizes she isn't actually sick and Dee Dee has lied all these years, Gypsy Rose exacts her revenge.